PEMBUATAN MEDIA PEMBELAJARAN HURUF HIJAIYAH PADA PLATFORM ANDROID MENGGUNAKAN METODE ADDIE - Abdul Rokhim; Muhammad Khairil Anwar (STMIK YADIKA BANGIL, 2021)
Abstract : Hijaiyah letters are letters used to read AL-Quran, so learning hijaiyah letters is a first step to reading the holy AL-Quran. While the Android system is an operating system that is in great demand by the world community, so it can be used as a tool to support learning how to read and write hijaiyah letters correctly and well. To increase interest in learning to read and write hijaiyah letters, the author developed a media application for learning to write 28 hijaiyah letters and how to read them on the android platform using the ADDIE method, where the addie method itself is very suitable for developing various products in learning activities such as models, learning strategies, learning methods, media and teaching materials.Keywords: Android, Hijaiyah, ADDIE,Read,Write.